Study on the Durability of Concrete under an Underwater Coupling Environment - Chunhua You; Gen He (Geofluids)
The durability of the concrete structure under the coupling effect of underwater corrosion particles has always been one of the hot issues at home and abroad. Aiming at the damage problem of the underground concrete structure in a marine and offshore chloride corrosion environment, based on the pile foundation engineering of the Coastal Industrial Park, the corrosion resistance test of pile foundation concrete is carried out. By preparing 7 kinds of pile foundation concrete samples with different mix proportions, the mechanical properties of concrete with different ages were analyzed under the coupling environment of groundwater. The chloride penetration resistance of concrete was analyzed by the RCM method, and the sulfate corrosion resistance was analyzed by the 17D accelerated simulation test. The test results show that with the decrease of the water-cement ratio and the increase of the cementitious material, the concrete damage is less and the durability is improved. It is suggested that the water-cement ratio of 0.34 and the cementitious material of 480 kg/m3 be selected for the preparation of the pile foundation concrete; when the content of fly ash is 15%, the antisulfuric acid corrosion ability of the concrete cementitious system can be enhanced and the concrete with 40% mineral powder has strong antichloride ion corrosion ability; the results show that the chloride diffusion coefficient of concrete samples with seven mix proportions is less than 6∗10–12 m2/s, which can meet the durability design requirements and reduce the damage of concrete. The sulfate corrosion resistance of concrete samples with high-efficiency additives is the best.